Gear efficiency estimation method through finite element and curve fitting - Mohd Ab Halim, Mohd Firdaus; Raja Othman, Raja Nor Firdaus Kashfi; Sulaiman, Erwan (IOS Press BV, 2021)
The inclusion of high energy density permanent magnet (PM) in MG contributes to the high eddy current loss in magnetic gear and reduces its efficiency. There was limited research done that focused on gear efficiency behavior over a broader range of speed and in different gear ratios. In this paper, the function of gear efficiency concerning gear ratio and rotational speed is proposed. Torque and eddy current loss data were obtained through transient magnetic analysis using finite element software at several rotational ranges and gear ratios. The analytical approach through mathematical substitution was discussed to confirm the finding in the simulation. The result showed that the gear efficiency decreases as the speed increases. Nonetheless, the gear efficiency revealed improvement in efficiency as the gear ratio increases. Finally, gear efficiency behavior was modeled using the curve fitting method. Subsequently, based on the correlation study, an equation was proposed, yielding a 1% error compared to the new simulated data. With this proposed method and equation, the analysis and estimation of gear efficiency behavior over wider speed and gear ratios are simplified, thus reducing the need to perform simulation over different speeds and gear ratios.